Liver metastases - An unusual cause of portal hypertension: A case report. (December 2022) - Pandey, Rajesh; Khanal, Sambhu; Neupane, Shashank; Dhakal, Bishal; Pudasaini, Prasamsa; Khadka, Sabina; Adhikari, Rupika; Poudel, Bipin
Abstract: Introduction: Portal hypertension is a rare complication of liver metastases. The study highlights that clinician should be aware of conditions mimicking cirrhosis with similar clinical presentation and imaging findings. Case presentation: We present the case of a 29-year-old non-alcoholic lady who presented to our hospital with a history of two months of progressive, painless abdominal distension and progressively increasing yellowish discoloration of the eyes. Physical examination, laboratory investigations, and imaging tests led to a diagnosis of multiple metastases from breast carcinoma to the liver leading to portal hypertension after exclusion of other causes of portal hypertension. However, after three weeks of presentation to the hospital, the patient died before any therapeutic measures were initiated to address breast carcinoma. Clinical discussion: Liver metastasis from primary breast carcinoma rarely presents with clinical symptoms of portal hypertension. Although portal hypertension secondary to pseudocirrhosis, predominantly linked to ongoing chemotherapy for known cancers, has been previously described in case studies, our case had an unusual presentation leading to diagnostic uncertainty. Conclusion: Our case highlights the rare cause of liver metastasis secondary to breast carcinoma, which presented as portal hypertension. Highlights: Portal hypertension is a rare complication of liver metastases, frequently occurring in malignant diseases. In patients with liver metastases, chemotherapy can result in areas of retracted tumor tissue and scarring, also known as pseudocirrhosis. Although portal hypertension is secondary to pseudocirrhosis and predominantly linked to ongoing chemotherapy for known cancers, our case had an unusual presentation leading to diagnostic uncertainty. The patient has an atypical presentation with symptoms consistent with portal hypertension and chronic liver disease without prior exposure to chemotherapy which could be due to the tumor deposits resulting in sinusoidal obstruction, subsequently leading to portal hypertension.